Determinants of Condom Use Status among Men Who Have Sex with Men (MSM) Group in 5 Indonesian Cities in 2015 - Ni Wayan Putri Larassita Parwangsa; Krisnawati Bantas (GHMJ (Global Health Management Journal), 2019)
Backgorund : Significant increase in HIV cases among men who have sex with men (hereafter MSM) group during the 2015-2016 period confirmed that sexual behavior is a major risk factor in exposure to HIV&AIDS with unprotected sexual intercourse as the dominant risk factor. Aims : This study aims to identify the determinants of condom use status  among MSM group in 5 cities in Indonesia. Method : This study used a cross sectional design, carried out in 5 cities in Indonesia: Jakarta, Bandung, Semarang, Surabaya, and Denpasar using secondary data from the Integrated Biological and Behavioural Survey (IBBS) in 2015. Results : Variables that are significantly related to the condom use status were marital status, exposure to information on HIV&AIDS, and knowledge about condoms. The marital status variable has a POR value of 1.351 (95% CI OR 0.709 – 2.576), whilst exposure to HIV&AIDS information has 1.668 (95% CI OR 1.148 – 2.422) POR value, and knowledge about condoms has POR value as much as 1.925 (95% CI OR 1.274 – 2.907). Conclusion : The number of respondents who used condoms consistently for the past one month were 76.1% and those who did not were 23.9%. Variables that are significantly related to the behaviour of not using condoms are marital status, exposure to HIV&AIDS information, and knowledge of condoms.Keywords:Determinants, Behavior, Condom, MSM, HIV&AIDS